1994
DOI: 10.1007/bf00868281
|View full text |Cite
|
Sign up to set email alerts
|

Prompt remission of post-renal transplant nephrotic syndrome with high-dose cyclosporine

Abstract: A 2.8-year-old girl with focal segmental glomerulosclerosis had recurrence of nephrotic syndrome within 3 days of renal transplantation and the serum creatinine increased. Renal biopsy showed cellular rejection and also complete effacement of the epithelial cell foot processes. The rejection responded to methylprednisolone therapy but massive proteinuria persisted. An increase in the dose of cyclosporine A to 14 mg/kg per day was followed by immediate remission of the proteinuria. One month later, a second ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Ingulli et al (18) reported two children with recurrent nephrotic syndrome after renal transplantation in whom proteinuria was controlled after high-dose oral CsA. Similarly, Srivastava et al (20) reported a rapid and sustained remission after high-dose oral CsA in a child with recurrent nephrotic syndrome after renal transplantation. Before beginning this study, we had observed remission of proteinuria in one child who had received IV CsA when it was part of our basic immunosuppressive protocol in the late 1980s.…”
Section: Discussionmentioning
confidence: 94%
“…Ingulli et al (18) reported two children with recurrent nephrotic syndrome after renal transplantation in whom proteinuria was controlled after high-dose oral CsA. Similarly, Srivastava et al (20) reported a rapid and sustained remission after high-dose oral CsA in a child with recurrent nephrotic syndrome after renal transplantation. Before beginning this study, we had observed remission of proteinuria in one child who had received IV CsA when it was part of our basic immunosuppressive protocol in the late 1980s.…”
Section: Discussionmentioning
confidence: 94%
“…The introduction of CsA has not in general significantly altered the rate of recurrence [2,5,21]. Some studies suggested that high-dose CsA given orally or intravenously may trigger long-term remissions [22][23][24][25]. This drug effect was attributed to modulation of the immune response or to reduction of glomerular filtration pressure leading to vasoconstriction or inhibition of a vascular permeability factor.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate is reported to be about 20% for transplanted FSGS patients [1,2]. The prognosis for recurrent FSGS is poor, as approximately one-third of patients progress to end-stage renal failure within 5 years [3,4,5,6,7]. There have been case reports and case series of certain effective treatments for FSGS recurrence, such as oral cyclophosphamide therapy, high-dose cyclosporine therapy, treatment with ACE inhibitors or/and angiotensin receptor antagonists, plasma exchange, and immunoabsorption [3,4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis for recurrent FSGS is poor, as approximately one-third of patients progress to end-stage renal failure within 5 years [3,4,5,6,7]. There have been case reports and case series of certain effective treatments for FSGS recurrence, such as oral cyclophosphamide therapy, high-dose cyclosporine therapy, treatment with ACE inhibitors or/and angiotensin receptor antagonists, plasma exchange, and immunoabsorption [3,4,8,9]. It has recently been reported that about 70% of recurrent FSGS responded to high-dose cyclosporine A or a combination of high-dose cyclosporine A and therapeutic plasma exchange, but about 20% of those patients failed to respond to the therapy and lost their grafts because of recurrent FSGS [8].…”
Section: Introductionmentioning
confidence: 99%